The influence of work discipline and work motivation on employee performance with job satisfaction as an intervening variable (a study at PT PLN (persero) generation control unit in Southern Sumatra sector of Keramasan) - Ayu Okti Sapira; Yos Karimudin; Muhammad Ichsan Hadjri; Agustina Hanafi; Yuliani, Yuliani (Jurnal Ekonomi, 2024)
This research aims to analyze the influence of work discipline and work motivation on employee performance with job satisfaction as an intervening variable. The study adopts a quantitative approach, and the sample consists of 87 permanent employees of PT PLN Persero Generation Control Unit in the Southern Sumatra Keramasan Sector. Data for the research is obtained through primary sources, utilizing offline questionnaires. The data analysis method employed in this study is Structural Equation Modeling (SEM) using the SmartPLS application. The results indicate that work discipline has a significantly positive effect on job satisfaction, while it has a significantly negative effect on employee performance. Work motivation has a significantly positive effect on employee performance. Additionally, work discipline has a significantly positive effect on employee performance mediated by job satisfaction, and work motivation has a significantly positive effect on employee performance mediated by job satisfaction.